2021
DOI: 10.1111/acel.13353
|View full text |Cite
|
Sign up to set email alerts
|

Declined miR‐181a‐5p expression is associated with impaired natural killer cell development and function with aging

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Finally, there are a number of studies reporting decreased levels of miR‐181 family members in the context of aging. For example, levels of specific miR‐181 homologs were found to be lower in serum from older individuals (Hooten et al, 2013), human naïve CD4+ T cells (Li, Yu, et al, 2012), murine NK cells (Lu et al, 2021), aged muscle (Mercken et al, 2013), and aged, calorie‐restricted brain tissue (Khanna et al, 2011). It will be interesting in future studies to explore the therapeutic potential of targeting miR‐181 homologs as a means to regulate immune cell responses, muscle function, chronic inflammation, bone repair, or other cellular processes that are known to be suppressed with increased age.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are a number of studies reporting decreased levels of miR‐181 family members in the context of aging. For example, levels of specific miR‐181 homologs were found to be lower in serum from older individuals (Hooten et al, 2013), human naïve CD4+ T cells (Li, Yu, et al, 2012), murine NK cells (Lu et al, 2021), aged muscle (Mercken et al, 2013), and aged, calorie‐restricted brain tissue (Khanna et al, 2011). It will be interesting in future studies to explore the therapeutic potential of targeting miR‐181 homologs as a means to regulate immune cell responses, muscle function, chronic inflammation, bone repair, or other cellular processes that are known to be suppressed with increased age.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-181a-5p was downregulated in aged NK cells, which inhibited NK cell development by reducing the production of IFNγ and the cytotoxicity of NK cells (Lu, Li, et al, 2021). MiR-181a was also downregulated in sarcopenia, an age-related loss of skeletal muscle mass and function, and negatively regulated myotube size (Soriano-Arroquia et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that reduced miR‐181a‐5p expression is associated with a series of age‐related disorders, including immune dysfunction (Kim et al, 2019 ; Lu, Li, et al, 2021 ), sarcopenia (Soriano‐Arroquia et al, 2016 ), and hearing loss (Zhang et al, 2013 ). For example, miR‐181a‐5p was downregulated in aged NK cells, which inhibited NK cell development by reducing the production of IFN‐γ and the cytotoxicity of NK cells (Lu, Li, et al, 2021 ). MiR‐181a was also downregulated in sarcopenia, an age‐related loss of skeletal muscle mass and function, and negatively regulated myotube size (Soriano‐Arroquia et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the healthy donors were not age-matched as their median age was significantly lower than those of COVID-19 patients (39 years in HCs versus 60 years and 64 years in ICU and WARD respectively, Supplementary Table 1 ). Studies described that older people have a decreased proportion of CD56 bright versus CD56 dim NK cells and a decreased capacity to produce cytokines, chemokines, and cytotoxic molecules ( 71 , 72 ). Therefore, in the present study, the numerical differences in NK cells between patients and HCs, but not their cytotoxic and cytokine-producing activities, may be attributed to age differences.…”
Section: Discussionmentioning
confidence: 99%